TEST RESULTS AND TECHNICO-ECONOMIC INDICATORS OF A GRAPEFRUIT TREE-PLANTING MACHINE (Modern American Journal of Biological and Environmental Sciences, 2025)
The article analyses the prototype of a pomegranate stem-cutter, its field trial results and its technical and economic indicators. The research established the machine's structural and technological advantages, its working efficiency, energy consumption, fuel economy, and economic efficiency. The trials conducted confirmed the machine's practical effectiveness, and it was recommended for production.